2008
DOI: 10.1002/jmv.21268
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Human herpesvirus 6 reactivation associated with colitis in a lung transplant recipient

Abstract: Whereas human herpesvirus 6 (HHV-6) reactivation is frequent in solid organ transplant recipients, symptomatic disease is rare. A case of colitis associated with HHV-6B reactivation was observed in a lung transplant recipient. This case report suggests that symptomatic HHV-6 infection may occur in the absence of detectable viremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
(23 reference statements)
0
14
0
1
Order By: Relevance
“…Likely, the main causes for upper gastrointestinal symptoms were H. pylori induced gastritis, gastro‐oesophageal reflux etc. Although there have been a few case reports describing HHV‐6 colitis [10–12], a recent study on HHV‐6 in over a thousand samples has demonstrated several cases with gastrointestinal biopsies infected with HHV‐6, mostly HHV‐6B and having significant clinical symptoms such diarrhoea, fever and colitis [31]. The experience of antiviral treatment of HHV‐6 infections is very limited and mostly based on the treatment of encephalitis [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely, the main causes for upper gastrointestinal symptoms were H. pylori induced gastritis, gastro‐oesophageal reflux etc. Although there have been a few case reports describing HHV‐6 colitis [10–12], a recent study on HHV‐6 in over a thousand samples has demonstrated several cases with gastrointestinal biopsies infected with HHV‐6, mostly HHV‐6B and having significant clinical symptoms such diarrhoea, fever and colitis [31]. The experience of antiviral treatment of HHV‐6 infections is very limited and mostly based on the treatment of encephalitis [7].…”
Section: Discussionmentioning
confidence: 99%
“…In stem cell transplant patients with gastrointestinal symptoms, HHV‐6 DNA has been detected by PCR in gastroduodenal and colorectal mucosa [8] and by in situ hybridization in large bowel mucosa [9]. Occasional case reports have described HHV‐6 associated colitis in lung and renal transplant recipients [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…HHV‐6B reactivation often occurs in immunocompetent individuals during drug induced hypersensitivity syndrome (DIHS) and the related drug rash with eosinophilia and systemic symptoms (DRESS). Symptoms and conditions that have been firmly associated with HHV‐6B in immunocompromised patients include exanthematous rash, fever, seizures , encephalopathy , limbic encephalitis and amnesia , cognitive dysfunction , lymphadenopathy , colitis , and hepatitis . Less well established, and in some cases controversial associations have been reported for Stevens–Johnson syndrome (SJS) , renal failure , hemophagocytic syndrome , myocarditis , pneumonitis , hypogammaglobulinemia , and arteriopathies .…”
Section: Introductionmentioning
confidence: 99%
“…Active infection by HHV‐6 and HHV‐7 in solid organ transplant recipients is usually asymptomatic. Overt clinical disease directly due to HHV‐6 is estimated to occur in less than 1% of solid organ transplant recipients , reportedly causing fever and rash , hepatitis , gastroduodenitis , colitis , pneumonitis , and encephalitis . It may also present as a CMV‐like syndrome, with fever and some degree of bone marrow suppression .…”
Section: Human Herpesviruses 6 Andmentioning
confidence: 99%